If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -5x + 2 = 0 Reorder the terms: -2 + 2 + -5x = 0 Combine like terms: -2 + 2 = 0 0 + -5x = 0 -5x = 0 Solving -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = 0 Simplifying x = 0
| 1/2[5-x]=1/4 | | -2xy^2(3x-2y)= | | 7z-6=5 | | x^3-8x+8=0 | | 10x-5=x+8 | | 9^-5x^4/9^-3x^-1= | | 7(u-6)=-7 | | 5x-3x-24=8x-2x+24 | | 43/29=24/x | | =32-[9-3(4-10)]+(2-5)3 | | 12+6x=8-4x | | 8[x+6]-3x=18 | | 18(v+1)-2v=4(4v+4)-21 | | 6(7x-8)=246 | | (-4x^2y)(3x^4)(-2xy^5)= | | 3+8z-12=2z-9+z | | 8(5x-11)=112 | | 5x^2+9x-165=0 | | 10(7x+14)=490 | | 6(7x+6)=246 | | -9(v+3)+2v+7=5v+11 | | Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 | | 15x-13=12x+41 | | 105-3t-32+8t-20=-72+6t-4 | | 2x+3x+3= | | -5=-3[x+11]-17 | | 7(5x-18)=259 | | 3(2x-9)=4(x+1) | | y=20+.9x | | 3(4.32x)+3.41y=65.48 |